THE EFFECT OF EASE AND SPEED ON INTEREST IN USING THE QRIS PAYMENT SYSTEM ON STUDENTS MAJORING IN MANAGEMENT, FACULTY OF ECONOMICS AND BUSINESS, UNIVERSITY OF MUHAMMADIYAH MAKASSAR - Sawir Wahyu; Nasrullah, Nasrullah; Sahrullah, Sahrullah (International Journal of Economic Research and Financial Accounting, 2024)
The purpose of this study is a type of quantitative research with the aim of determining the effect of ease and speed on interest in using the QRIS payment system on students majoring in Management, Faculty of Economics and Business, University of Muhammadiyah Makassar. Samples were taken from students majoring in Management, Faculty of Economics and Business, University of Muhammadiyah Makassar. The type of data used in this study is quantitative data obtained from questionnaires that are shared and relate to the problem under study. Data collection is carried out by observation and distribution of questionnaires. In this study, the data sources used in data collection include primary data and secondary data. The research instrument used in this study used the Likert scale method. The results showed that data using statistical calculations through the Statistical Package for the Social Science (SPSS) version 26 application at the stage of data collection, data management, and data analysis regarding the effect of convenience and speed on interest in using the QRIS payment system in students majoring in management, faculty of economics and business, University of Muhammadiyah Makassar, it can be concluded that convenience has a positive and significant effect The interest in using in students majoring in management, faculty of economics and business, University of Muhammadiyah Makassar, and speed has a negative and significant effect on interest in using in students majoring in management, faculty of economics and business, University of Muhammadiyah Makassar.